Liquid crystal polymer composition and molded article prepared from same
By optimizing the ratio and particle size of mica, wollastonite and distearyl phosphate potassium salts in the liquid crystal polymer composition, the welding strength and dust generation problems of liquid crystal polymer materials in the prior art are solved, and a liquid crystal polymer composition with high rigidity, depression resistance and low dust generation is achieved.
Patent Information
- Application Number
- CN202380051138.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-05-31
- Publication Date
- 2025-02-28
AI Technical Summary
Existing mobile devices such as compact camera module components made of liquid crystal polymer-based materials may cause image defects or failures due to contact with the CMOS sensor by particles and/or dust generated by the material, and low welding strength, resulting in equipment failures.
A liquid crystal polymer composition is developed, including liquid crystal polymers, mica, wollastonite and distearyl phosphate potassium salts, to improve welding strength, rigidity and depression resistance and reduce dust generation by optimizing the proportion and particle size of these components.
The liquid crystal polymer composition with excellent welding strength, rigidity and depression resistance is achieved, which reduces dust generation and improves the reliability and performance of the equipment.
Smart Images

Figure BDA0005219635310000121 
Figure BDA0005219635310000122 
Figure BDA0005219635310000131
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal polymer composition and a molded product prepared from the composition. More specifically, the present invention relates to a liquid crystal polymer composition having excellent welding strength, rigidity, dent resistance, etc. and less dust generation and a molded product prepared from the composition. Background Art
[0002] Recently, with the development of the electronics and communications fields, mobile devices with highly integrated complex structures and thin-walled components are being produced. In such mobile devices, compact camera module applications are made using liquid crystal polymer (LCP)-based materials, which are excellent in heat resistance and dimensional stability and can be molded into thin walls.
[0003] However, mobile devices such as compact camera module components manufactured from liquid crystal polymer-based materials may suffer from image defects or autofocus and optical jitter correction failures due to particles and / or dust generated from the materials contacting CMOS (complementary metal oxide semiconductor) sensors, and may also cause failure of the entire device due to low weld strength.
[0004] Therefore, there is an urgent need to develop a liquid crystal polymer composition that is excellent in welding strength, rigidity, and dent resistance and generates less dust.
[0005] The background art of the present invention is disclosed in Korean Patent No. 10-1423766 and the like. Summary of the invention
[0006] An object of the present invention is to provide a liquid crystal polymer composition which is excellent in welding strength, rigidity, dent resistance, etc. and generates less dust.
[0007] Another object of the present invention is to provide a molded article formed from the liquid crystal polymer composition.
[0008] The above-mentioned object and other objects of the present invention can be achieved by the present invention described below.
[0009] 1. One aspect of the present invention relates to a liquid crystal polymer composition, which comprises: about 100 parts by weight of a liquid crystal polymer; about 10 parts by weight to about 40 parts by weight of mica; about 5 parts by weight to about 30 parts by weight of wollastonite; and about 0.1 parts by weight to about 2 parts by weight of potassium distearyl phosphate.
[0010] 2. In the aforementioned specific example 1, the crystal melting point of the liquid crystal polymer may be 280°C to 360°C.
[0011] 3. In the specific example of item 1 or 2 above, the average particle size of the mica may be about 15 μm to about 35 μm.
[0012] 4. In the specific examples of items 1 to 3 above, the cross-sectional diameter of the wollastonite may be about 1 μm to about 10 μm, and the length after processing may be about 30 μm to about 40 μm.
[0013] 5. In the specific examples of items 1 to 4 above, the weight ratio of the mica to the wollastonite may be about 1:0.2 to about 1:1.5.
[0014] 6. In the specific examples of items 1 to 5 above, the weight ratio of the mica to the potassium distearyl phosphate may be about 1:0.01 to about 1:0.1.
[0015] 7. In the specific examples 1 to 6 above, the welding strength of a 9mm×9mm×3mm sample of the liquid crystal polymer composition measured by a push-pull device at a speed of 0.5mm / s can be about 8.6N to about 20N.
[0016] 8. In the above-mentioned specific examples 1 to 7, the flexural modulus of a sample of the liquid crystal polymer composition having a thickness of 1 / 4" measured at a speed of 2.8 mm / min according to ASTM D790 may be about 120,000 kgf / cm 2 To about 140,000kgf / cm 2 .
[0017] 9. In the specific examples of items 1 to 8 above, after a ball point tip (tungsten carbide) with a diameter of 0.65 mm is attached to an aluminum rod (total weight of 40 g) and dropped from a height of 3 cm onto a sample of the liquid crystal polymer composition with a thickness of 3.2 mm, the surface dent depth measured by an optical profilometer can be about 10 μm to about 20 μm.
[0018] 10. In the specific examples of items 1 to 8 above, a sample of the liquid crystal polymer composition in the shape of a Lego block with eight protrusions and measuring 32 mm × 16 mm × 9 mm is placed in a drum measuring 30 cm × 30 cm × 100 cm, and after the drum is rotated 2,000 times at 7 rpm for evaluation, the dust generation amount measured according to the following formula 1 is approximately 1,000 ppm to approximately 3,500 ppm.
[0019] [Formula 1]
[0020] Dust generation = (W1-W2) / W1
[0021] In Formula 1, W1 is the weight of the sample before the roller evaluation, and W2 is the weight of the sample after the roller evaluation.
[0022] 11. Another aspect of the present invention relates to a molded article, wherein the molded article is formed from the liquid crystal polymer composition according to any one of items 1 to 10 above.
[0023] 12. In the specific example of item 11 above, the molded product may be a compact camera module component.
[0024] The present invention has the effect of providing a liquid crystal polymer composition which is excellent in welding strength, rigidity, dent resistance, etc. and generates less dust, and a molded product formed from the composition. DETAILED DESCRIPTION
[0025] Hereinafter, the present invention is described in detail as follows.
[0026] The liquid crystal polymer composition of the present invention comprises: a liquid crystal polymer (A); mica (B); wollastonite (C); and distearyl potassium phosphate (D).
[0027] In the present specification, “a to b” indicating a numerical range is defined as “≥a and ≤b”.
[0028] Liquid crystal polymer (A)
[0029] A specific example of the present invention is a liquid crystal polymer (LCP) that exhibits an anisotropic melt phase, and liquid crystal polyester amides and liquid crystal polyesters, which are called thermotropic liquid crystal polymers, can be used. Here, the anisotropic melt phase of the liquid crystal polymer can be confirmed by a conventional polarization system method using a right-angle polarizer (light polarizer). For example, in a nitrogen atmosphere, a sample on a Leitz hot plate can be observed by a Leitz polarizing microscope.
[0030] In a specific example, the liquid crystal polymer may include repeating units such as aromatic oxycarbonyl, aromatic dicarbonyl, aromatic dioxy, aromatic aminooxy, aromatic aminocarbonyl, aromatic diamino, aromatic oxydicarbonyl, aliphatic dioxy, and combinations thereof.
[0031] In a specific example, the liquid crystal polymer composed of the above repeating units may include a liquid crystal polymer providing an anisotropic melting phase and a liquid crystal polymer not providing an anisotropic melting phase, depending on the structural elements, ratios and arrangement distribution of the polymer. The liquid crystal polymer used in the present invention exhibits an anisotropic melting phase.
[0032] In a specific example, examples of monomers providing aromatic oxycarbonyl repeating units are 4-hydroxybenzoic acid, m-hydroxybenzoic acid, o-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4'-hydroxybiphenyl-4-carboxylic acid, 3'-hydroxybiphenyl-4-carboxylic acid, 4'-hydroxybiphenyl-3-carboxylic acid, and derivatives thereof substituted with alkyl, alkoxy or halogen, acyl derivatives thereof, ester derivatives thereof, and ester-forming derivatives of acyl halides. From the viewpoint of being easier to adjust the properties and melting point of the generated liquid crystal polymer, 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid are preferred among the above substances.
[0033] In a specific example, examples of monomers providing aromatic dicarbonyl repeating units are aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 4,4'-dicarboxybiphenyl, and derivatives thereof substituted with alkyl, alkoxy or halogen, ester derivatives thereof, and ester-forming derivatives of acid halides. From the viewpoint of easier adjustment of mechanical properties, heat resistance, melting point, and molding properties of the generated liquid crystal polymer, terephthalic acid and 2,6-naphthalene dicarboxylic acid are preferred among the above substances.
[0034] In a specific example, examples of monomers providing aromatic dioxy repeating units are aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, and ester-forming derivatives thereof such as alkyl, alkoxy or halogen-substituted derivatives thereof and acyl derivatives thereof. Among the above substances, hydroquinone and 4,4'-dihydroxybiphenyl are preferred from the viewpoint of good reactivity during the polymerization process and good properties of the resulting liquid crystal polymer complex.
[0035] In a specific example, examples of monomers providing aromatic aminooxy repeating units are aromatic hydroxylamines such as p-aminophenol, m-aminophenol, N-acetyl-4-aminophenol, 4-amino-1-naphthol, 5-amino-1-naphthol, 8-amino-2-naphthol, 4-amino-4'-hydroxybiphenyl, derivatives thereof substituted by alkyl, alkoxy or halogen, ester-forming derivatives of its acyl derivatives, and amide-forming derivatives such as its N-acyl derivatives.
[0036] In a specific example, examples of monomers providing aromatic diamino repeating units are aromatic diamines such as p-phenylenediamine, m-p-phenylenediamine, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, their derivatives substituted by alkyl, alkoxy or halogen, and amide-forming derivatives such as their N-acyl derivatives.
[0037] In a specific example, examples of monomers providing aromatic aminocarbonyl repeating units are aromatic aminocarboxylic acids such as p-aminobenzoic acid, m-aminobenzoic acid, 6-amino-2-naphthoic acid, derivatives thereof substituted by alkyl, alkoxy or halogen, acyl derivatives thereof, ester derivatives and ester-forming derivatives of acid halides, and amide-forming derivatives such as N-acyl derivatives thereof.
[0038] In a specific example, examples of monomers providing aromatic oxydicarbonyl repeating units are hydroxy-aromatic dicarboxylic acids such as 3-hydroxy-2,7-naphthalene dicarboxylic acid, 4-hydroxyisophthalic acid, 5-hydroxyisophthalic acid, and ester-forming derivatives thereof such as alkyl, alkoxy or halogen-substituted derivatives thereof, acyl derivatives thereof, ester derivatives thereof and acyl halides.
[0039] In a specific example, examples of monomers providing aliphatic dioxy repeating units are aliphatic diols such as ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and acyl derivatives thereof. In addition, a liquid crystal polymer having aliphatic dioxy repeating units can be obtained by reacting a polyester having aliphatic dioxy repeating units such as polyethylene terephthalate or polybutylene terephthalate with the aromatic oxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxylamine, aromatic aminocarboxylic acid, aromatic diamine, or acyl derivatives thereof, ester derivatives thereof, or acid halides thereof.
[0040] In a specific example, the liquid crystal polymer may have a thioester bond if the bonding does not impair the purpose of the present invention. Examples of monomers providing thioester bonds are mercapto-aromatic carboxylic acids, aromatic dithiols, and hydroxy-aromatic thiols. The ratio of these additional monomers is preferably about 10 mol% or less based on the total amount of monomers providing aromatic oxycarbonyl, aromatic dicarbonyl, aromatic dioxy, aromatic aminooxy, aromatic diamino, aromatic oxydicarbonyl, and aliphatic dioxy repeating units.
[0041] Among the above, a preferred liquid crystal polymer used in the present invention comprises an aromatic oxycarbonyl repeating unit comprising a 4-oxybenzoyl repeating unit and / or a 6-oxy-2-naphthoyl repeating unit.
[0042] In a specific example, examples of preferred liquid crystal polymers including 4-oxybenzoyl and / or 6-oxy-2-naphthoyl repeating units may include the following:
[0043] 1) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid copolymer;
[0044] 2) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl copolymer;
[0045] 3) 4-hydroxybenzoic acid / terephthalic acid / isophthalic acid / 4,4'-dihydroxybiphenyl copolymer;
[0046] 4) 4-hydroxybenzoic acid / terephthalic acid / isophthalic acid / 4,4'-dihydroxybiphenyl / hydroquinone copolymer;
[0047] 5) 4-hydroxybenzoic acid / terephthalic acid / hydroquinone copolymer;
[0048] 6) 6-hydroxy-2-naphthoic acid / terephthalic acid / hydroquinone copolymer;
[0049] 7) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl copolymer;
[0050] 8) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / N-acetyl-4-aminophenol copolymer;
[0051] 9) 6-hydroxy-2-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl copolymer;
[0052] 10) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / hydroquinone copolymer;
[0053] 11) 4-hydroxybenzoic acid / 2,6-naphthalene dicarboxylic acid / 4,4'-dihydroxybiphenyl copolymer;
[0054] 12) 4-hydroxybenzoic acid / terephthalic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone copolymer;
[0055] 13) 4-hydroxybenzoic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone copolymer;
[0056] 14) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone copolymer;
[0057] 15) 4-hydroxybenzoic acid / terephthalic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone / 4,4'-dihydroxybiphenyl copolymer;
[0058] 16) 4-hydroxybenzoic acid / terephthalic acid / 4-aminophenol copolymer;
[0059] 17) 6-hydroxy-2-naphthoic acid / terephthalic acid / 4-aminophenol copolymer;
[0060] 18) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / 4-aminophenol copolymer;
[0061] 19) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / 4-aminophenol copolymer;
[0062] 20) 4-Hydroxybenzoic acid / terephthalic acid / ethylene glycol copolymer;
[0063] 21) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / ethylene glycol copolymer;
[0064] 22) 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / ethylene glycol copolymer; and
[0065] 23) 4-Hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / ethylene glycol copolymer.
[0066] From the viewpoint of the moldability and mechanical properties of the polymer, copolymers of 1), 8), 9) and 13) are preferred among the above.
[0067] In a specific example, in order to improve the fluidity of the polymer during molding, the liquid crystal polymer may be a polymer complex including two or more liquid crystal polymers.
[0068] In a specific example, the preparation method of the liquid crystal polymer is not limited, and any method known in the art can be used. For example, a conventional polycondensation method can be used, such as a slurry polymerization method and a melt acid hydrolysis method for preparing a polymer to generate an ester bond and / or an amide bond in the monomer elements described above.
[0069] In a specific example, the melt acid hydrolysis method is preferably used for the preparation of liquid crystal polymers. In this method, after the monomers are heated to form a molten solution, the solution is reacted to form a molten polymer. The final step of this method can be performed under vacuum to facilitate the removal of volatile by-products such as acetic acid or water.
[0070] In a specific example, the slurry polymerization method is characterized in that monomers are reacted in a heat exchange fluid to generate a solid polymer in the form of a suspension in the heat exchange liquid medium.
[0071] In a specific example, in any case of the melt acidolysis method or the slurry polymerization method, the polymerized monomer can be in the form of a lower acyl derivative obtained by acylation of the hydroxyl group and / or the amino group. The lower acyl group can have 2 to 5 carbon atoms, for example, 2 to 3 carbon atoms. Preferably, an acetylated monomer is used in the reaction.
[0072] In a specific example, the lower acyl derivative of the monomer may be prepared by independently acylating the monomer in advance, or may be generated in a reaction system by adding an acylating agent such as acetic anhydride to the monomer when preparing the liquid crystal polymer.
[0073] In a specific example, in any case of the melt acidolysis process or the slurry polymerization process, a catalyst may be used in the reaction, if necessary.
[0074] In a specific embodiment, examples of catalysts include: organic tin compounds such as dialkyl tin oxides (e.g., dibutyl tin oxide) and diaryl tin oxides; antimony trioxide; titanium dioxide; organic titanium compounds such as alkoxy titanium silicates and alkoxy titanium salts; alkali metal salts or alkaline earth metal salts of carboxylic acids such as potassium acetate; inorganic acid salts (e.g., K2SO4); and gaseous acid catalysts such as Lewis acids (e.g., BF3) and hydrogen halides (e.g., HCl).
[0075] In a specific example, when a catalyst is used, the amount of the catalyst added to the reaction may be about 10 ppm to about 1000 ppm, such as about 20 ppm to about 200 ppm, based on the total amount of monomers.
[0076] In a specific example, the liquid crystal polymer can be obtained from a reaction vessel in which the polymer is polymerized in a molten state, and then processed to generate pellets, flakes or powders.
[0077] In a specific example, if necessary, the liquid crystal polymer in the form of particles, flakes or powder can be heated to a substantially solid state in a vacuum or inert gas atmosphere such as nitrogen or helium. The heat treatment temperature can be about 260°C to about 350°C, for example, about 280°C to about 320°C.
[0078] In a specific example, the crystalline melting point (Tm) of the liquid crystal polymer determined by differential scanning calorimetry may be about 280° C. to about 360° C. The method of determining the crystalline melting point is as follows.
[0079] Use a differential scanning calorimeter (DSC) Exstar 6000 (Seiko Instruments Inc., Chiba, Japan) or a DSC device of the same type. Heat the liquid crystal polymer sample to be tested from room temperature at a rate of 20°C / min and measure the endothermic peak (Tm1). Then, keep the sample at a temperature 20°C to 50°C higher than Tm1 for 10 minutes. Next, cool the sample to room temperature at a rate of 10°C / min and then heat it at a rate of 10°C / min. The endothermic peak found in the final step is recorded as the crystalline melting point (Tm) of the sample liquid crystal polymer.
[0080] Mica(B)
[0081] Mica, a specific example of the present invention, can be used together with wollastonite and potassium distearyl phosphate to improve the welding strength, rigidity and dent resistance of the liquid crystal polymer composition, and reduce dust generation. Conventional flaky mica can be used.
[0082] In a specific example, the average particle size of the mica measured by a particle size tester (Malvern mastersizer 3000) may be about 15 μm to about 35 μm, for example, about 20 μm to about 30 μm. Within the above range, the surface appearance of the liquid crystal polymer composition may be excellent.
[0083] In a specific example, about 10 parts by weight to about 40 parts by weight, such as about 15 parts by weight to about 30 parts by weight, of the mica may be included relative to about 100 parts by weight of the liquid crystal polymer. When the content of the mica is less than about 10 parts by weight relative to about 100 parts by weight of the liquid crystal polymer, the welding strength, rigidity, etc. of the liquid crystal polymer composition (molded article) may decrease, and when the content of the mica exceeds about 40 parts by weight, the liquid crystal polymer composition (molded article) may generate a large amount of dust.
[0084] Wollastonite (C)
[0085] Wollastonite, a specific example of the present invention, can be used together with mica and potassium distearyl phosphate to improve the welding strength, rigidity and dent resistance of the liquid crystal polymer composition, and reduce dust generation. Conventional needle-shaped wollastonite can be used.
[0086] In a specific example, the wollastonite is a calcium mineral and a white needle-shaped mineral, and at least a portion of its surface is subjected to a hydrophobic surface treatment. Here, the hydrophobic surface treatment may include, for example, coating the wollastonite with an olefin, epoxy or silane substance, but is not limited thereto.
[0087] In a specific example, the cross-sectional diameter of the wollastonite measured by a particle size tester (Malvern mastersizer 3000) may be about 1 μm to about 10 μm, for example, about 2 μm to about 9 μm, and the length before processing may be about 50 μm to about 80 μm, and the length after processing may be about 20 μm to about 50 μm, for example, about 30 μm to about 40 μm. Within the range, the welding strength, rigidity, etc. of the liquid crystal polymer composition may be excellent.
[0088] In a specific example, about 5 parts by weight to about 30 parts by weight, such as about 8 parts by weight to about 23 parts by weight, may be included relative to about 100 parts by weight of the liquid crystal polymer. When the content of the wollastonite is less than about 5 parts by weight relative to about 100 parts by weight of the liquid crystal polymer, the rigidity of the liquid crystal polymer composition (molded product) may decrease, and when the content of the wollastonite exceeds about 30 parts by weight, the liquid crystal polymer composition (molded product) may generate a large amount of dust.
[0089] In a specific example, the weight ratio (B:C) of the mica (B) to the wollastonite (C) may be about 1:0.2 to about 1:1.5, for example, about 1:0.25 to about 1:1.4. Within the above range, the mechanical strength of the liquid crystal polymer composition (molded product) may be more excellent, and dust generation may be reduced.
[0090] Distearyl Phosphate Potassium Salt (E)
[0091] Potassium distearyl phosphate, which is a specific example of the present invention, can be used together with mica and wollastonite to improve the welding strength, rigidity, and dent resistance of a liquid crystal polymer composition, and reduce dust generation.
[0092] In a specific example, about 0.1 to about 2 parts by weight, for example, about 0.2 to about 1 part by weight of the potassium distearyl phosphate may be included relative to about 100 parts by weight of the liquid crystal polymer. When the content of the potassium distearyl phosphate is less than about 0.1 parts by weight relative to about 100 parts by weight of the liquid crystal polymer, the welding strength, rigidity, and dent resistance of the liquid crystal polymer composition (molded article) may decrease, and when the content of the potassium distearyl phosphate exceeds about 2 parts by weight, the rigidity of the liquid crystal polymer composition (molded article) may decrease.
[0093] In a specific example, the weight ratio (B:D) of the mica (B) to the potassium distearyl phosphate (D) may be about 1:0.01 to about 1:0.1, for example, about 1:0.01 to about 1:0.05. Within the above range, the welding strength, rigidity, and dent resistance of the liquid crystal polymer composition (molded article) may be more excellent.
[0094] A liquid crystal polymer composition of a specific example of the present invention may further include additives included in conventional liquid crystal polymer compositions. Examples of the additives include antioxidants, anti-drip agents, lubricants, release agents, nucleating agents, antistatic agents, stabilizers, pigments, dyes, mixtures thereof, etc., but are not limited thereto. When the additives are used, the content of the additives may be from about 0.001 parts by weight to about 40 parts by weight, for example, from about 0.1 parts by weight to about 10 parts by weight, relative to about 100 parts by weight of the liquid crystal polymer.
[0095] The liquid crystal polymer composition of a specific example of the present invention may be in the form of pellets by mixing the components and melt-extruding at about 330° C. to about 360° C., for example, about 340° C. to about 350° C. using a conventional twin-screw extruder.
[0096] In a specific example, the welding strength of a 9mm×9mm×3mm sample of the liquid crystal polymer composition measured by using a push-pull device (manufacturer: IMADA, device name: MX-500N, push-pull gauge: IMADA DST500N) and pulling at a speed of 0.5mm / s in the direction of producing the welding line can be about 8.6N to about 20N, for example, about 8.8N to about 15N.
[0097] In a specific example, the flexural modulus of a sample having a thickness of 1 / 4" of the liquid crystal polymer composition measured at a speed of 2.8 mm / min according to ASTM D790 may be about 120,000 kgf / cm 2 To about 140,000kgf / cm 2, for example, about 123,000 kgf / cm 2 To about 139,000kgf / cm 2 .
[0098] In a specific example, after a ball point tip (tungsten carbide) with a diameter of 0.65 mm is attached to an aluminum rod (total weight of 40 g) and dropped from a height of 3 cm onto a sample of the liquid crystal polymer composition with a thickness of 3.2 mm, the surface dent depth measured by an optical profilometer can be about 10 μm to about 20 μm, for example, about 11 μm to about 19 μm.
[0099] In a specific example, a 32 mm×16 mm×9 mm Lego block-shaped sample of the liquid crystal polymer composition having eight protrusions is placed in a 30 cm×30 cm×100 cm drum and rotated 2,000 times at 7 rpm for drum evaluation. The dust generation amount measured according to the following formula 1 can be about 1,000 ppm to about 3,500 ppm, for example, about 1,100 ppm to about 3,300 ppm.
[0100] [Formula 1]
[0101] Dust generation = (W1-W2) / W1
[0102] In Formula 1, W1 is the weight of the sample before the roller evaluation, and W2 is the weight of the sample after the roller evaluation.
[0103] The molded article of the present invention is formed by the liquid crystal polymer composition. The liquid crystal polymer composition can be made into a particle form, and the prepared particles can be made into various molded articles (products) by various molding methods such as injection molding, extrusion molding, vacuum molding, casting molding, etc. This molding method is well known to those with general knowledge in the field to which the present invention belongs. The molded article has excellent welding strength, rigidity, dent resistance, etc., and generates less dust, which is conducive to the manufacture of surface-mounted electronic components including switches, relays, connectors, concentrators, coils, transformers, camera modules, antennas and chip antenna switches, as well as components installed using lead-free solder processed at higher temperatures. For example, the molded article can be a compact camera module component, etc.
[0104] The present invention will be described in more detail below by way of examples, but these examples are only for illustration and should not be construed as limiting the present invention.
[0105] Example
[0106] The specifications of the components used in the following examples and comparative examples are as follows.
[0107] Liquid crystal polymer (A)
[0108] A 4-hydroxybenzoic acid / 6-hydroxy-2-naphthoic acid / terephthalic acid / 4,4′-dihydroxybiphenyl / N-acetyl-4-aminophenol copolymer (cas no. 147310-94-9, manufacturer: Seyang Polymer, product name: SEYANG LCPG600BB) was used.
[0109] Flaky inorganic filler (B)
[0110] (B1) Mica (manufacturer: Yamaguchi Mica, product name: AB25S, average particle size: 25 μm) was used.
[0111] (B2) Talc (manufacturer: KOCH, product name: KCEP-400, average particle size: 12 μm) was used.
[0112] Needle-shaped inorganic filler (C)
[0113] (C1) Wollastonite (manufacturer: FJS, product name: WFC5-4101, cross-sectional diameter: 6 μm, length after processing: 40 μm) was used.
[0114] (C2) Glass fiber (manufacturer: NITTOBO, product name: CSG 3PA-832, cross section: rectangular (a=28 μm, b=7 μm), length after processing: 350 μm).
[0115] Phosphorus compounds (D)
[0116] (D1) Potassium distearyl phosphate (manufacturer: ADEKA, product name: ADK STAB AX-71) was used.
[0117] (D2) Sodium acid pyrophosphate (manufacturer: Innophos, product name: SAPP) was used.
[0118] Examples 1 to 9 and Comparative Examples 1 to 9
[0119] After adding the above-mentioned components in the amounts described in the following Tables 1, 2, 3 and 4, pellets were prepared by extrusion at 350°C. The pellets were extruded using a twin-screw extruder with L / D=44 and a diameter of 45 mm. After drying the pellets at 80°C for more than 4 hours, the pellets were injection molded in a 150T injection molding machine (molding temperature: 340°C, mold temperature: 100°C) to prepare samples. The physical properties of the prepared samples were evaluated according to the following methods, and the results are shown in the following Tables 1, 2, 3 and 4.
[0120] Physical property measurement method
[0121] (1) Weld strength (unit: N): A 9 mm × 9 mm × 3 mm sample was pulled in the direction of the weld line at a speed of 0.5 mm / s using a push-pull device (manufacturer: IMADA, device name: MX-500N, push-pull gauge: IMADA DST500N), and the peak force (peak force, weld strength) of the sample was measured.
[0122] (2) Flexural modulus (unit: kgf / cm 2 ): The flexural modulus of a specimen with a thickness of 1 / 4" was measured at a speed of 2.8 mm / min according to ASTM D790.
[0123] (3) Surface dent depth (unit: μm): After a ball point tip (tungsten carbide) with a diameter of 0.65 mm was attached to an aluminum rod (total weight of 40 g) and dropped from a height of 3 cm onto a sample with a thickness of 3.2 mm, the surface dent depth was measured using an optical profiler (optical profiler, manufacturer: VEECO, equipment name: Veeco Wyko NT1100 Optical Profiling System).
[0124] (4) Dust generation (unit: ppm): A Lego block-shaped sample with eight protrusions measuring 32 mm × 16 mm × 9 mm was placed in a tumbler measuring 30 cm × 30 cm × 100 cm and rotated 2,000 times at 7 rpm. The dust generation of the sample was calculated according to the following formula 1.
[0125] [Formula 1]
[0126] Dust generation = (W1-W2) / W1
[0127] In Formula 1, W1 is the weight of the sample before the roller evaluation, and W2 is the weight of the sample after the roller evaluation.
[0128] [Table 1]
[0129]
[0130] [Table 2]
[0131]
[0132] [Table 3]
[0133]
[0134] [Table 4]
[0135]
[0136] The above results show that the liquid crystal polymer composition of the present invention is excellent in soldering strength, rigidity (flexural modulus), dent resistance (depth of surface dents), etc., and generates less dust.
[0137] On the contrary, in the case of Comparative Example 1 using a small amount of mica, it is known that the welding strength, rigidity, etc. are reduced; in the case of Comparative Example 2 using an excessive amount of mica, it is known that a large amount of dust is generated; in the case of using talc (B2) instead of the mica of the present invention (Comparative Example 3), it is known that the welding strength, rigidity, and anti-sag properties are reduced, and a large amount of dust is generated. In the case of Comparative Example 4 using a small amount of wollastonite, it is known that the rigidity is reduced; in the case of Comparative Example 5 using an excessive amount of wollastonite, it is known that a large amount of dust is generated; in the case of using glass fiber (C2) instead of the wollastonite of the present invention (Comparative Example 6), it is known that a large amount of dust is generated. In addition, in the case of Comparative Example 7 using a small amount of distearyl potassium phosphate, it can be seen that the welding strength, rigidity, and dent resistance are reduced; in the case of Comparative Example 8 using an excessive amount of distearyl potassium phosphate, it can be seen that the rigidity is reduced, and it is found that the appearance characteristics are reduced; in the case of using sodium acid pyrophosphate (D2) instead of the distearyl potassium phosphate of the present invention (Comparative Example 9), it can be seen that the welding strength, rigidity, and dent resistance are reduced.
[0138] The present invention has been discussed so far with the embodiments as the center. A person with general knowledge in the technical field to which the present invention belongs should understand that the present invention can be implemented by a deformed form within the scope of the essential characteristics of the present invention. Therefore, the disclosed embodiments should be taken from an illustrative point of view, not from a restrictive point of view. The scope of the present invention is shown in the claims, not in the foregoing description, and all differences within the scope equivalent thereto should be interpreted as being included in the present invention.
Claims
1. A liquid crystal polymer composition, characterized in that include: About 100 parts by weight of liquid crystal polymer; About 10 parts by weight to about 40 parts by weight of mica; From about 5 parts by weight to about 30 parts by weight of wollastonite; and Distearyl phosphate potassium salt is present in an amount of about 0.1 parts by weight to about 2 parts by weight.
2. The liquid crystal polymer composition according to claim 1, characterized in that The liquid crystal polymer has a crystalline melting point of 280°C to 360°C.
3. The liquid crystal polymer composition according to claim 1 or 2, characterized in that: The average particle size of the mica is about 15 μm to about 35 μm.
4. The liquid crystal polymer composition according to any one of claims 1 to 3, characterized in that The wollastonite has a cross-sectional diameter of about 1 μm to about 10 μm, and a processed length of about 30 μm to about 40 μm.
5. The liquid crystal polymer composition according to any one of claims 1 to 4, characterized in that The weight ratio of the mica to the wollastonite is about 1:0.2 to about 1:1.
5.
6. The liquid crystal polymer composition according to any one of claims 1 to 5, characterized in that The weight ratio of the mica to the potassium distearyl phosphate is about 1:0.01 to about 1:0.
1.
7. The liquid crystal polymer composition according to any one of claims 1 to 6, characterized in that The welding strength of a 9 mm×9 mm×3 mm sample of the liquid crystal polymer composition measured while being pulled at a speed of 0.5 mm / s using a Push-Pull device is about 8.6 N to about 20 N.
8. The liquid crystal polymer composition according to any one of claims 1 to 7, characterized in that The flexural modulus of a specimen having a thickness of 1 / 4" of the liquid crystal polymer composition measured at a speed of 2.8 mm / min according to ASTM D790 was about 120,000 kgf / cm 2 To about 140,000kgf / cm 2 .
9. The liquid crystal polymer composition according to any one of claims 1 to 8, characterized in that After a tungsten carbide ball point tip with a diameter of 0.65 mm was attached to an aluminum rod to make a total weight of 40 g and dropped from a height of 3 cm onto a sample of the liquid crystal polymer composition with a thickness of 3.2 mm, the surface dent depth measured by an optical profiler was about 10 μm to about 20 μm.
10. The liquid crystal polymer composition according to any one of claims 1 to 9, characterized in that A 32 mm×16 mm×9 mm Lego brick-shaped sample of the liquid crystal polymer composition having eight protrusions was placed in a 30 cm×30 cm×100 cm drum and subjected to drum evaluation by rotating 2,000 times at 7 rpm. The dust generation amount measured according to the following formula 1 was about 1,000 ppm to about 3,500 ppm. [Formula 1] Dust generation = (W1-W2) / W1 In Formula 1, W1 is the weight of the sample before the roller evaluation, and W2 is the weight of the sample after the roller evaluation.
11. A molded product, characterized in that: The molded article is formed from the liquid crystal polymer composition according to any one of claims 1 to 10.
12. The molded article according to claim 11, characterized in that The molded product is a compact camera module component.